Effect of Substitution of Wheat with Maize on Technological and Organoleptic Properties of Chapatties - Raza, Saeeda; Kanwal, Saima; Naseem, Khalid; Bibi , Naseem; Bibi , Amina (Asian Journal of Agriculture and Rural Development, 2014)
Unleavened flat bread (chapatti) was prepared from wheat (Tritium aestivum) and maize (Zea mays) composite flour. The wheat flours from mill and grindstone were collected from local market and blended with maize flour in 100:0, 90:10, 80:20 proportions. Technological and rheological studies revealed that gluten, falling number and water absorption values decreased with increased maize proportion. Increased dough development time by addition of 20% maize flour for either flour types was observed. Decrease in dough stability was observed by increased maize proportion in grindstone flour but in mill flour decrease with 10% maize and increase with 20% maize is noted. Overall Farinographic quality was highest in 20% blend of maize in grindstone flour. Chapatties were prepared and subjected to organoleptic tests by a panel of trained judges and 20% blend get maximum acceptability.